Atmospheric corrosion of weathering steels. Overview for engineers. Part II: Testing, inspection, maintenance. (20th October 2019) - Morcillo, M.; Díaz, I.; Cano, H.; Chico, B.; de la Fuente, D.
Highlights: Methods to evaluate the protective ability of rust layers on weathering steels (WS). Corrosion problems in WS structures. Testing, inspection and maintenance of WS structures. Advanced WS. Painting of WS. Abstract: The atmospheric corrosion of weathering steel (WS) has been extensively discussed in the scientific literature, but a comprehensive overview of this topic from an engineering viewpoint is currently lacking. The present publication seeks to fill this gap, providing engineers, designers and steel manufacturers with an insight into the current state of knowledge on this important structural material and presenting key research findings in a way that promotes their practical application. The Part II of this review sets out the methods available to evaluate the protective ability of rust layers and describes testing, inspection and maintenance techniques. The paper ends with a number of examples of corrosion problems in WS structures, an overview of new advanced WS, and considers the painting of WS in highly corrosive atmospheres.